Analysis of Irrigation Water Quality in The Susoh Irrigation Area, Southwest Aceh Regency, Province of Aceh - Helmi, Helmi; Syakur, Syakur (Universitas Serambi Mekkah, 2025)
The density of residential areas, especially in the Susoh Sub-District with a population of 24,440, has led to several issues, including increased pollution from domestic and agricultural waste, which affects irrigation water quality. This study aims to assess the water quality classes in the Susoh Irrigation Area, covering the water flow from the upstream to the downstream part of its drainage system. This study employed a quantitative descriptive method through field surveys, sample collection, and laboratory analysis. The results showed that the Electrical Conductivity (EC) ranged from 88.04–93.60 mS-cm (classified as excellent), pH ranged from 6.08–7.13 (amazing), Sodium (Na) ranged from 2.12–3.23 mg-l, Chloride (Cl) from 3.05–3.56 mg-l(excellent), and Sulphate (SO4) was 1.5 mg-l (excellent), based on Scofield’s (1936) irrigation water quality standards.